Respuesta :

[tex]\boxed{ \sf{Answer}} [/tex]

[tex]\sf \: g(x) = {x}^{2} - 4 \\ \\ \sf \: x = 5 \\ \\ \sf \: g(5) = {5}^{2} - 4 \\ \sf \: g(5) = 25 - 4 \\ \sf \: g(5) =\underline 2\underline1[/tex]

Answer ↦21 [Option C]

[tex]\tt \: g(x) = {x}^{2} - 4[/tex]

Substitute the value of x as 5 (given) in the above equation. The equation changes too..

[tex]\tt \: g(5) = {5}^{2} - 4[/tex]

Now you can easily solve the equation.

[tex]\tt \: g(5) = {5}^{2} - 4 \\\tt g(5) =( 5 \times 5) - 4 \\ \tt \: g(5) = 25 - 4 \\ \tt \: g(5) = 21[/tex]

Answer - [tex]\boxed{\sf{21}}[/tex]